Good spirit of the old bridge - Mehmedbasic, Nada ([S.l.] : FTU BiH (production company), [S.l.] : Journeyman Pictures, 2003)
This video documented the thought and memories of those seeking to recapture the good spirit of the Old Bridge. The Old Bridge is located at River Neretva, Mostar, Bosnia.
Actors: Emir Balic, Benard Kalajdzic, Hans Dzemat, Samir Zukanovic, Irfan Fink
Keywords: Bridges -- Bosnia and Herzegovina -- Mostar -- History; Mostar(Bosnia and Herzegovina) -- History